Pembelajaran Berbasis Teknologi dan Inovasi Digital: Transformasi, Implementasi, dan Tantangannya di Era Modern - Sitompul, Siti Rohima; Masrum, Nailul Muna Salsabila; Saksitha, Deassy Arestya (Indonesian Journal of Islamic Educational Management, 2023)
Pembelajaran Berbasis Teknologi dan Inovasi Digital: Transformasi, Implementasi, dan Tantangannya di Era ModernTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//